Documentation of the status of international geothermal power plants and a list by country of selected geothermally active governmental and private sector entities - United States. Department of Energy. (National Geothermal Association, Davis, CA (United States), 1992)
This report includes the printouts from the International Geothermal Power Plant Data Base and the Geothermally Active Entity Data Base. Also included are the explanation of the abbreviations used in the power plant data base, maps of geothermal installations by country, and data base questionnaires and mailing lists.